CARA DETEKSI YODIUM SEMI-KUANTITATIF SEDERHANA PADA GARAM RUMAH TANGGA: UJI KELAYAKAN DI LAPANGAN - Suryana Purawisastra; Sukati Saidin; Djoko Kartono; Dhuto Widagdo (Persagi, 2009)
A Simple Field Kit-Test For Semi-Quantitative Iodine Content In The Iodated Salt of Households: An Appropriate-Test In The Field.Background: A programme of iodized salt for human consumption has been in operation in Indonesia for over 3 decades. Effectiveness of the programmed is to control and regular monitoring of edible salt for iodine. Therefore, it is required a simple field kit for semi quantitative estimation of iodine content in the iodated salt in the households.Methods: Thetest was performed by forty-five of house wives and forty-five of